(untitled) (Research, Society and Development, 2021)
This article presents a scoping review protocol on the aspects that further or limit the implementation of care for Sexual and Reproductive Health of the LGBTQIA + community in the Unified Health System (SUS), directing at proposing recommendations to strengthen and ensure the exercise of sexual and reproductive rights of this community. The protocol aims to document the processes involved in the planning and methodological construction of the scoping review, the same was oriented by the guidelines of the Joanna Briggs Institute (JBI). The review protocol did develop following the PRISMA Extension for Scoping Reviews (PRISMA-ScR): Checklist and Explanation. The same remained registered in the Open Science Framework.